PENINGKATAN HASIL BELAJAR PPKn DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS IV SD NEGERI 010 BANJAR PANJANG KECAMATAN KERUMUTAN - Achmad Ikrom (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the author's experience teaching for this in SD Negeri 010 Banjar Panjang, andbased on observation and early reflections by the author, see the low creativity of students inlearning that ultimately ends up in the low student learning outcomes themselves, especiallyon subjects PPKn. After many tests on the midterm turns lower student learning outcomes.Completeness class only reach 50% or 20 out of 40 students, KKM for subjects PPKnspecified in Class IV SD Negeri 010 Banjar Panjang is the number 70. The purpose of thisresearch is to increase learning outcomes Lessons eye PPKn with the adoption of thedemonstration. This research is a classroom action research (PTK). Class Action Researchthrough the stages of planning, implementation, observation and reflection. This study wasconducted in 010 primary schools in Banjar Long Lessons 2016. As the subjects in this studyis the fourth grade students SD Negeri 010 Banjar Panjang . The research was conducted inthe fourth grade SD Negeri 010 Banjar Panjang, whereas a study carried out in April. 2016.From the results of actions, obtained PPKn student learning outcomes of action onpreliminary data for the first cycle to the second cycle with improved student learningoutcomes with significant menigkat, the preliminary data of students who achieve masteryonly 50% and cycle to the first increase has reached 70% and the thoroughness of the class inthe second cycle reaches 85%.